PD-L1 is highly expressed in lung lymphoepithelioma-like carcinoma: A potential rationale for immunotherapy. Issue 3 (June 2015) - Chang, Yih-Leong; Yang, Ching-Yao; Lin, Mong-Wei; Wu, Chen-Tu; Yang, Pan-Chyr
Highlights: PD-L1 refers to a target for immunotherapy of NSCLC, but its role in LELC is unclear. LELC is highly associated with EBV infection. Driver mutations are infrequent in LELC. Our data first show that PD-L1 expression is a common feature (75.8%) in LELC. These findings may provide a rationale for immunotherapy in LELC. Abstract: Objectives: Programmed cell death-ligand 1 (PD-L1) and driver mutations are found in non-small cell lung cancers (NSCLCs) and may be suitable targets for specific therapies, but their roles in lymphoepithelioma-like carcinoma (LELC) of the lung are unclear. Materials and methods: Sixty-six patients with pulmonary LELCs were investigated. Paraffin-embedded tumor sections were stained with PD-L1 antibody. Tumors with moderate-to-strong membrane staining in ≥5% of tumor cells were positive for PD-L1 overexpression. The presence of driver mutations in the genes for epidermal growth factor receptor ( EGFR ), KRAS, and BRAF were examined by direct sequencing. Anaplastic lymphoma kinase (ALK) and ROS1 levels were determined by immunohistochemistry. Correlations of PD-L1 expression and driver mutations with clinicopathologic parameters were analyzed. Results: The overall frequency of PD-L1 overexpression and EGFR mutation was 75.8% and 12.1%, respectively. No KRAS, BRAF, ALK or ROS1 aberrations could be detected. PD-L1 expression was not associated with driver mutations. Multivariate analysis revealed that smoking and advanced stage were independent risk factors for poor overall survival, whereas PD-L1 positivity was not significantly associated with patient outcome. Conclusion: There are high PD-L1 expression and infrequent driver mutations in LELCs compared with conventional NSCLCs. The high expression of PD-L1 in EBV and inflammation associated LELC may provide a rationale for immunotherapy in this subtype of lung cancer.